1994
DOI: 10.3354/meps115021
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations of the ectoparasites of seven reef fish species from Lizard Island and Heron Island, Australia

Abstract: Spat~al and temporal variations in abundance of ectoparasites from 7 coral reef fish species [Hemigyrnnus melapterus (Labridae), Siganus doliatus (Siganidae), Scolopsis bilinea tus (Nemipteridae), Thalassoma lunare (Labridae), Scarus sordidus (Scaridae), Ctenochaetus stn'atus (Acanthuridae), and Acanthochromis polyacanthus (Pomacentridae)] at 2 locations, Lizard Island and Heron Island in the Great Barner Reef, were investigated. The study demonstrates that there is a significant species-specific parasite faun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 17 publications
4
131
1
Order By: Relevance
“…Grutter (1994) found a positive correlation between host fish length and gnathiid parasite loads. Rózsa (1997) showed that wingfeather mite abundance correlates with the body mass of their bird hosts.…”
Section: Introductionmentioning
confidence: 80%
“…Grutter (1994) found a positive correlation between host fish length and gnathiid parasite loads. Rózsa (1997) showed that wingfeather mite abundance correlates with the body mass of their bird hosts.…”
Section: Introductionmentioning
confidence: 80%
“…Because the data from Bshary (2001) suggest that changes in service quality may vary according to a client"s value as a food patch, we recorded client size as a correlate of this value (Bshary 2001, Grutter 1994). …”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…A close correlation between host size and parasite richness has been previously demonstrated in rabbitfish (e.g., Grutter 1994;Martens and Moens 1995). This relationship is particularly relevant as far as the heteroxenous species are concerned (Digeneans, Acanthocephala and many species of nematodes) since they accumulate but cannot proliferate on the host.…”
Section: Parasitological Parameter Evaluationmentioning
confidence: 58%